BIG DATA ANALYTICS: APPLICATIONS, PROSPECTS AND CHALLENGES (Journal of Medical & Health Sciences Review, 2025)
Big Data Analytics helps organizations to reveal previously unknown patterns, trends and other correlations that could not be obtained with the help of conventional data processing systems. The 21st-century surge in digital information led to the emergence of Big Data Analytics a collection of technologies and practices that are intended to manage, process and analyze large volumes of information with high volume, velocity and variety. Its uses in integrating BDA cut across various segments such as healthcare, which uses it in diagnosing diseases and promoting personalized medicine and  finance. It detects fraud and manage risks; and retail, where customer behavior is studied to improve service delivery. The purpose of this paper is to offer an in-depth review of the present uses of Big Data Analytics. It looks at the future trends and opportunities, and critically evaluate the obstacles that hinder its wider adoption and successful use. This study is a qualitative one, as it will employ various techniques of data collection to develop in-depth ideas about Big Data Analytics. These expert opinions offered helpful insights concerning the challenges encountered as well as the innovation that is propelling the field. It is a fact that Big Data Analytics is an enthusiast of innovation, efficacy and a competitive advantage in the digital era. Its use in different industries has already revealed its usefulness in resolving complicated problems and the improvement of the decision-making process.